Branchenspezifische Besonderheiten im Innovationsver-halten des Ernaḧrungsgewerbes: Eine empirische Analyse des Mannheimer Innovationspanels - Sabine Kubitzki; Sven Anders (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2005)
Ziel dieser Arbeit ist eine vergleichende Untersuchung des Innovationsverhaltens im verarbeitenden Gewerbe anhand eines Querschnittsdatensatzes des Mannheimer Innovationspanels. Die Besonderheiten des Ernährungsgewerbes werden durch eine kombinierte Analyse von Innovationsinput- und Outputindikatoren mittels linearen und logistischen Regressionen überprüft. Die Literaturanalyse zeigt, dass das Ernährungsgewerbe mit einer relativ kurzen Entwicklungszeit von durchschnittlich 8,5 Monaten im Vergleich zu anderen Branchen überwiegend Produktmodifikationen hervorbringt. Ein großer Teil der eingeführten Innovationen wird zudem umgehend durch Wettbewerber imitiert, so dass kaum Monopolrenten abgeschöpft werden. Darüber hinaus weist das Ernährungsgewerbe im Branchenvergleich sehr niedrige Aufwendungen für Forschung und Entwicklung (F&E) als Anteil an den Innovationsaufwendungen auf. Der Import an Forschung aus technologieintensiveren Branchen ist hingegen sehr hoch. Intersektoral zeigt das Ernährungsgewerbe überdurchschnittliche Marketingaktivitäten bei der Einführung neuer Produkte... (Quelle: Verlag) – – The article's aim is to conduct a comparative cross-section analysis of the innovative behaviour of the German manufacturing industry. The peculiarities of the food industry are tested in a combined analysis based on both input and output indicators. Linear and logistic regressions are used to investigate the differences between the food industry and other branches of the manufacturing industry. In comparison to other branches, the food industry has lower research & development (R&D) expenditures whereas the import of research from more technology intensive sectors is high. Most of the released new products are improvements and imitations. Market novelties are rare. The development time for new products is relatively short compared to other industries, on average 8.5 months. A major part of innovations are imitated rapidly by competing firms, therefore the first mover advantages are low. Due to the low newness of innovations, marketing activities (e.g. advertising, labelling) are more important for new product introductions than in other industries. The regression analysis for the input indicators measured by the innovation intensity shows that the innovative behaviour of food companies significantly deviates from other manufacturing sectors. However, the logistic regression analysis of the output indicators doesn't confirm these results. The dummy variable of the food companies has no significant impact on the output indicators. Firms in the food industry might embark on imitation and product modification strategies. Therefore, they realize an average innovation output without spending the same amount of money as the other industries. In addition, it can be confirmed that small enterprises of the German manufacturing industry have a higher innovation activity in terms of both innovation input and output. The impact of business expectations on input and output indicators is significantly positive. An international orientation measured by the ratio of exports to firm sales leads to a higher probability of introducing new products and novelties.
Keywords: 330; Ernährungsindustrie; Innovation; Industrieforschung; Deutschland